A New Analytical Q-Absorbance Ratio Method Development and Validation for Simultaneous Estimation of Lamivudine and Isoniazid. (16th December 2013) - Pandey, Gitu; Mishra, Brahmeshwar
Abstract : A new UV spectrophotometric absorption ratio method was developed and validated for the simultaneous estimation of lamivudine and isoniazid. The method involved Q -absorption ratio analysis using two wavelengths, with one being the λ max of lamivudine (272 nm, λ 2 ) and the other being the isoabsorptive point of both drugs (246 nm, λ 1 ). Beer's law was obeyed in the concentration range between 5 and 30  µ g/mL for both lamivudine and isoniazid. The results of analysis have been validated statistically and by recovery studies as per ICH guidelines. The accuracy ranged between 99.65 and 101.91% and Sandell's sensitivity ranged between 0.0229 and 0.0347  µ g/cm 2 . The method was found to be simple, precise, reproducible, rapid, and economical. Hence, it could be used in the analysis of laboratory samples and marketed formulations containing these two drugs in the future.